Boron deficiency decreased the root activity of Ga-exposed rice seedlings by reducing iron accumulation and increasing Ga in iron plaque - Ren, Wei-Lin (Ecotoxicology (London, England), 2024)
© 2024. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.